2012
DOI: 10.1007/s11248-012-9611-5
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of artificial microRNAs targeting Grapevine fanleaf virus and evidence for RNA silencing in grapevine somatic embryos

Abstract: Grapevines are affected worldwide by viruses that compromise fruit yield and quality. Grapevine fanleaf virus (GFLV) causes fanleaf degeneration disease, a major threat to grapevine production. Transgenic approaches exploiting the RNA silencing machinery have proven suitable for engineering viral resistance in several crop species. However, the artificial microRNA (amiRNA)-based strategy has not yet been reported in grapevine. We developed two amiRNA precursors (pre-amiRNAs) targeting the coat protein (CP) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 47 publications
0
31
0
1
Order By: Relevance
“…This also provides a straightforward method for transient expression assays. Up to now, these assays, based on short‐term high‐level expression of transgenes after cocultivation, mainly involved somatic embryos selected at the mid‐cotyledonary stage of development of Thompson seedless (Li et al ., , , , ) and Chardonnay (Jelly et al ., ). Naturally colourless embryos are particularly convenient for monitoring the expression of fluorescence‐ (Li et al ., & Li et al ., ) and colour‐based reporter genes (Jelly et al ., ; Li et al ., ).…”
Section: Methods For Gene Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…This also provides a straightforward method for transient expression assays. Up to now, these assays, based on short‐term high‐level expression of transgenes after cocultivation, mainly involved somatic embryos selected at the mid‐cotyledonary stage of development of Thompson seedless (Li et al ., , , , ) and Chardonnay (Jelly et al ., ). Naturally colourless embryos are particularly convenient for monitoring the expression of fluorescence‐ (Li et al ., & Li et al ., ) and colour‐based reporter genes (Jelly et al ., ; Li et al ., ).…”
Section: Methods For Gene Transfermentioning
confidence: 99%
“…New synthetic promoters were tested in Thompson seedless somatic embryos using gus and gfp (Li et al ., and Li et al ., ). To validate amiRNA constructs designed to control virus infection, a GUS‐based RNAi reporter was used in somatic embryos of Chardonnay (Jelly et al ., ).…”
Section: Dna Constructsmentioning
confidence: 97%
See 1 more Smart Citation
“…12B). However, the most significant impact of X. index is a result of its activity as the vector of Grapevine fanleaf virus (GFLV) (Hewitt et al, 1958), one of the most important viruses of grapevine (Jelly et al, 2012). Virus particles are attached to the cuticular lining and lumen of the odontophore and the pharynx.…”
Section: Xiphinema Indexmentioning
confidence: 99%
“…Indeed several studies demonstrated that artificial miRNAs (amiRNAs) targeting key components of the viral replication machinery can efficiently impair viral growth upon infection [59][60][61][62][63][64][65]. These efforts have revealed that such resistance is cell-autonomous, inheritable, more efficient than siRNA-mediated strategies and successful in blocking viral replication and movement [59,66].…”
Section: Sncrnas and Viruses: New Frontiers Of Defensementioning
confidence: 99%